(untitled) (Cambridge, 1998)
This book crystallizes a new field of scholarship that studies the creation of distinct environments as a result of the interaction of human social systems with the natural world. Pioneering essays explore new methodologies of historical environmental research, comparisons of China with the West and Japan, and the impact of the early modern ecological transformation on the spread of disease. An indispensable book for those trying to understand the foundations of modern China or the origins of many of contemporary China's most daunting challenges.
Keywords: Ecology,Ecology,Environmental sciences,Sinh thái học,Sinh thái học,Khoa học môi trường; China,Trung Quốc